Investigation of a dichlorodioxomolybdenum(VI)-pyrazolylpyridine complex and a hybrid derivative as catalysts in olefin epoxidation - Amarante, Tatiana R.
Treatment of the solvent adduct [MoO2Cl2(THF)(2)] with the ligand 2-(1-pentyl-3-pyrazolyl)pyridine (1, abbreviated as pent-pp) gave the dioxomolybdenum(VI) complex [MoO2Cl2(pent-pp)] (2), which was characterised by elemental analysis, H-1 NMR, FT-IR spectroscopy and single crystal X-ray diffraction (XRD). Reaction of 2 with water in a Teflon-lined stainless steel autoclave at 100 degrees C led to the isolation of a molybdenum oxide/pyrazolylpyridine hybrid material with the composition [Mo2O6(pent-pp)] (3), which was characterised by variable temperature powder XRD, scanning electron microscopy, thermogravimetric analysis, FT-IR and C-13H-1 CP MAS NMR spectroscopies. Compounds 2 and 3 display high activity and selectivity when used as (pre) catalysts for the epoxidation of cis-cyclooctene at 55 degrees C with tert-butylhydroperoxide as an oxidant. Further catalytic experiments with 3 as a (pre) catalyst were performed using the bio-derived olefins DL-limonene (Lim) and methyl oleate (Ole). The reaction of Lim gave mainly 1,2-epoxy-p-menth-8-ene and 1,2; 8,9-diepoxy-p-menthane in a combined yield of 93% at 97% conversion (6 h), while the reaction of Ole led to 9,10-epoxystearate as the main product in 78% yield at 82% conversion (6 h). The catalytic reactions are homogeneous in nature. Starting with material 3, the oxodiperoxo complex [MoO(O-2)(2)(pent-pp)] (4) was isolated from solution after a catalytic run, suggesting that it is formed from 3 and plays a catalytic role.